2019
DOI: 10.12669/pjms.35.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of serum matrix metalloproteinases among patients of oral squamous cell carcinoma

Abstract: Objective: To estimate the serum levels of matrix metalloproteinases in oral squamous cell carcinoma patients and in healthy subjects. Methods: In this observational study, biopsy diagnosed oral squamous cell carcinoma patients (n= 38) were recruited from Mayo Hospital, Lahore during 2016 to 2017. Age and gender matched Controls (n= 38) were also included. Venous blood sample of each participant was drawn, serum separated and the levels of matrix metalloproteinases were measured by multiplex ELISA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“… 17 A study by Choudhry et al found six proteinases (MMP-1, -2, -8, -10, -12, and -13) with significant differential expression in the serum of the oral squamous cell carcinoma (OSCC) patients and healthy controls. 18 Among them, the MMP-12 had the highest AUC of 0.836 (95% CI : 0.733-0.911) with a sensitivity and specificity of 80.0% and 78.9%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“… 17 A study by Choudhry et al found six proteinases (MMP-1, -2, -8, -10, -12, and -13) with significant differential expression in the serum of the oral squamous cell carcinoma (OSCC) patients and healthy controls. 18 Among them, the MMP-12 had the highest AUC of 0.836 (95% CI : 0.733-0.911) with a sensitivity and specificity of 80.0% and 78.9%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The degradation of the extracellular matrix and basement membrane requires the participation of matrix metallopeptidases (MMPs). Numerous studies have described the relationship between MMPs and OSCC, which is primarily involved in tumor progression, invasion and metastasis, and poor prognosis [103][104][105]. Integrins are cell adhesion molecules that mediate the interaction between cells and the extracellular matrix and regulate a variety of functions, including cell motility, invasion, proliferation, and migration [106,107].…”
Section: Tissue Invasion and Metastasismentioning
confidence: 99%
“…Until now, several oral salivary biomarkers have been studied but not enough data is available for a biomarker that could aid in primary OSCC detection at the non-detectable stage or precursor stage [12].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying a biomarker may serve threefold bene ts; detection of the tumour at an early stage, serving as a prognostic marker and a therapeutic target [12]. Matrix metalloproteinase (MMPs) are considered one of those potential biomarkers that can theoretically ful l all these purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation